2021
DOI: 10.3390/pharmaceutics13111969
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effect of Energy Density and Formulation Factors on the Printability and Characteristics of SLS Irbesartan Tablets—Application of the Decision Tree Model

Abstract: Selective laser sintering (SLS) is a rapid prototyping technique for the production of three-dimensional objects through selectively sintering powder-based layer materials. The aim of the study was to investigate the effect of energy density (ED) and formulation factors on the printability and characteristics of SLS irbesartan tablets. The correlation between formulation factors, ED, and printability was obtained using a decision tree model with an accuracy of 80%. FT-IR results revealed that there was no inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 59 publications
(97 reference statements)
0
4
0
Order By: Relevance
“…In Figure 5 , the X-ray diffractograms of CVD blends post-SLS at different laser intensities show haloes, indicating the absence of CVD crystallinity. To the best of our knowledge, only Madžarević et al have reported the transformation of an API into an amorphous state as a result of SLS processing for the formation of printed tablets [ 39 ]. The findings suggested that for the polymer and drug used in this study, the SLS printing of solid dosage forms may be able to produce an amorphous solid dispersion, increasing the apparent solubility of the API [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 5 , the X-ray diffractograms of CVD blends post-SLS at different laser intensities show haloes, indicating the absence of CVD crystallinity. To the best of our knowledge, only Madžarević et al have reported the transformation of an API into an amorphous state as a result of SLS processing for the formation of printed tablets [ 39 ]. The findings suggested that for the polymer and drug used in this study, the SLS printing of solid dosage forms may be able to produce an amorphous solid dispersion, increasing the apparent solubility of the API [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…SEM analyses revealed that the SLS samples built with medium energy density had the lowest porosity both on the surface and in the cross section. According to Madžarević et al [ 149 ], the energy density is also a critical process parameter in the SLS printing of biopolymers for solid dosage forms (tablet production) because it affects the physical, mechanical, and morphological characteristics of the tablets. The effects of the process parameters (laser power, scan speed, hatch spacing, and scan length) on mechanical properties (strength, modulus of elasticity, and elongation) of PA12 samples as well as economic aspects of the SLA process can be found in [ 150 ].…”
Section: Manufacturing Parameters For Am Of Advanced Biopolymersmentioning
confidence: 99%
“…Since the mass of the printed structures is strongly temperature-dependent [16], this difference might have an effect on crucial properties of the dosage forms such as the dose of the API. Furthermore, the API can be amorphized unevenly which may cause changes in solubility of the API [17][18][19].…”
Section: Single Layer Printingmentioning
confidence: 99%